CRIMINAL ACTS OF CORRUPTION (BRIBE) BY PRIVATE HOSPITAL AGAINST A MIDWIFE IN REWARD FOR SERVICES FOR PATIENT REFERRAL - sutrisno, achmad; Soekorini, Noenik (Jurnal Independent, 2023)
The term bribe in corruption cases is a bribe or money given to another party to facilitate certain goals. People in Indonesia refer to bribes as facilitation payments. Cases of bribery have been going on for a long time in Indonesia. Bribes are usually given to officials in the government bureaucracy who have important roles, law enforcers, as well as customs and tax officials. Ironically, cases of bribery are still considered common in Indonesia.The results of a survey at the "MM" Hospital in November 2022 showed that midwives get a caesarean patient referral fee with BPJS of Rp. II in the amount of Rp. 600,000, - ; Class I Rp.700.000,-; VIP class Rp.800.000,-. Whereas there was an incident at the hospital where the patient could not pay off the payment, the patient was advised to be referred to the hospital by the midwife, and it was known that the midwife received a fee from the hospital.From the interview, there was a criminal act of bribery between the midwife and the hospital, which is referred to as bribery according to RI Law Number 11 of 1980 concerning the crime of bribery, article 1 which reads "Whoever receives or gets something from someone with the intention of persuading that person to do something or not. doing something in their duties, contrary to their authority or obligation which concerns the public interest, shall be punished for giving bribes with imprisonment for a maximum of 5 (five) years and a maximum fine of Rp. 15,000,000.- (fifteen million rupiahs).Legal responsibility for midwives and doctors, namely in the form of administrative sanctions based on Minister of Health Regulation No.58 of 2016 concerning sponsorship for health workers in the form of verbal warnings, revocation of licenses and also criminal sanctions based on the Corruption Crime Act, namely fines and imprisonment Keywords: Bribery, midwife referral